Modern Microwave Polarizers and Their Electromagnetic Characteristics - Shuliak, Vadym; Piltyay, Stepan; Bulashenko, Andrew; Zabegalov, Igor; Bulashenko, Oleksandr (2021 IEEE 3rd Ukraine Conference on Electrical and Computer Engineering (UKRCON), 2021)
In this paper we carry out the review of modern microwave waveguide polarizers, describe their main types, investigate their operation theoretical foundations and obtain analytically the formulas for calculation of their fundamental electromagnetic characteristics. Two theoretical techniques for the decomposition of an electromagnetic wave with any polarization type into two independent components with orthogonal polarizations are described. There are several equivalent characteristics of polarization purity estimation. The most frequently used characteristics are the axial ratio, cross polarization isolation and differential phase shift introduced by the investigated waveguide polarizer. The matching of the waveguide polarizer is characterized by voltage standing wave ratio or by the return losses of the structure. There exists the effect of influence of the matching quality on polarization state of the electromagnetic wave at the output of any waveguide polarizer. Consequently, the differential phase shift can't be applied as a single characteristic of the polarization performance of a waveguide device. For the improvement and clarification of the characteristics of polarization state of electromagnetic wave we have introduced the amplitudes of transmitted through the structure waves into the theoretical formulas of the axial ratio and cross polarization isolation of the microwave waveguide devices. Obtained rigorous mathematical formulas for polarization characteristics can be widely used for the development of various microwave polarization processing devices including orthomode transducers and waveguide polarizers of modern satellite information systems and radars.